Verification of the Integrative Model of Adjustment to Chronic Conditions by Mapping it Onto the World Health Organization's International Classification of Function, Disability and Health. (October 2022) - Hammond, Lis Dreijer; Farrington, Alexander Paul; Sivan, Manoj
Purpose: Literature regarding the WHO's International Classification of Function, Disability and Health (ICF) has called for research into psychosocial adjustment processes. This project aims to establish the relevance of the Integrative Model of Adjustment to Chronic Conditions (IMACC) as a framework for research and a clinical tool in rehabilitation by linking it with the ICF. Methods: The study employed secondary analysis of data from the original IMACC grounded theory study, where 8 women and 2 men with type 2 diabetes mellitus participated. IMACC consists of 3 interconnected parts comprising a total of 13 components. Datasets used for the study consisted of the qualitative data underpinning each IMACC component. Meaningful concepts from each dataset were linked to ICF categories using the updated ICF linking rules. Results: Results showed that all 13 IMACC components accommodate ICF category codes from all health and health related ICF components in patterns consistent with the theoretical conceptualisation of each separate IMACC component. Conclusion: IMACC maps comprehensively to the ICF framework and provides a framework that may be useful for future ICF related research into biopsychosocial processes in psychosocial adjustment. IMACC provides a clinically applicable intervention for people with psychosocial adjustment difficulties consistent with the ICF framework.